Mechanical behaviour of femur and humerus at the three-point bending and axial compression tests in the crab-eating fox (Cerdocyon thous, Linnaeus 1776) (Research, Society and Development, 2022)
The aim of the present study was to evaluate the mechanical behaviour of the femur and humerus of Cerdocyon thous through three-point bending and axial compression tests. For this, 13 femurs and 15 humerus were used in the bending test, and 14 femurs and 15 humerus in the compression test; after the assays were completed, bone fragments were collected for evaluation by means of conventional optical and polarized light microscopy, and scanning electron microscopy. It was observed that the humerus is more resistant in relation to the femur in both tests, and that bone length and weight, in addition to the width of the diaphysis, are influential on the mechanical behaviour. Microscopic evaluation showed that, on the cranial surface of the fractured bones under flexion, the fracture was caused by the deflection mechanism, while the caudal surface was ruptured by delamination. In bones submitted to axial compression, diaphyseal fractures occurred by deflection, while physeal fractures were caused by several mechanisms. There was no significant correlation between the arrangement of collagen fibres or mineral content on the mechanical properties obtained in both assays. It can be concluded that there are significant differences in the mechanical behaviour of the femur and humerus of C. thous, where the humerus is more resistant than the femur in both flexion and compression loads. Such data allow us to predict the bone mechanical behaviour of C. thous in the face of trauma caused by flexion and compression impacts, such as those resulting from running over.